PENGARUH KINERJA KEUANGAN, KEBIJAKAN DIVIDEN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Muhammad Ibnu Rafi (2021)
This research is a quantitative study that aims to analyze the effect of financial performance, dividend policies and investment decisions on firm value. In this research, the population is the manufacturing company on IDX during the priode 2016 to 2019. Thus research used the Stratified Random Sampling by using the Slovin formula and collected a sample of 144 research data. The hypothesis in this research was tested by Multiple Linear Regression Analysis techniques with a significance level of 5%. The results obtained from this research are financial performance, & dividend policies have a positive significant effect on firm value, and investment decisions have no effect on firm value.